2022
DOI: 10.1108/ijppm-06-2021-0325
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation, sustainability practices and performance of small and medium enterprises: evidence from an emerging economy

Abstract: PurposeDespite the growing scholarly interest in examining entrepreneurial orientation (EO)-performance link, the results have been inconsistent. However, studies have not explored firm-level and external factors that may serve as mechanisms or boundary conditions to explain this relationship. Therefore, the purpose of the study is to examine how and when EO influences performance by incorporating sustainability practices as a mechanism and competitive intensity as an important contingent factor.Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 100 publications
(235 reference statements)
0
2
1
Order By: Relevance
“…This study also strengthens the results of previous research conducted by Ismail (2023), which states that environmental orientation variables have a positive and significant effect on sustainable business performance. The results of this study are reinforced by the research of Akomea et al (2022), Souto (2022, and Danso et al (2022), who found the results of environmental orientation variables have a positive and significant effect on sustainable business performance that it can be concluded that high environmental orientation has a positive and significant influence on sustainable business performance.…”
Section: The Effect Of Environmental Orientation On Sustainable Busin...supporting
confidence: 54%
“…This study also strengthens the results of previous research conducted by Ismail (2023), which states that environmental orientation variables have a positive and significant effect on sustainable business performance. The results of this study are reinforced by the research of Akomea et al (2022), Souto (2022, and Danso et al (2022), who found the results of environmental orientation variables have a positive and significant effect on sustainable business performance that it can be concluded that high environmental orientation has a positive and significant influence on sustainable business performance.…”
Section: The Effect Of Environmental Orientation On Sustainable Busin...supporting
confidence: 54%
“…Third, unlike previous studies [95,136], it is demonstrated that TO, following SO, has a strong positive impact on OBP. It is observed that enterprises are becoming interested in implementing technology and innovation policies and practices.…”
Section: Discussioncontrasting
confidence: 81%
“…Entrepreneurship orientation is a psychological construct that reflects the intention toward entrepreneurial opportunities in light of risks and uncertainty (Makhloufi et al , 2021). Previous studies have shown that entrepreneurial orientation positively influences family firm performance (Hernández-Linares et al , 2020) and affects the performance of SMEs (Akomea et al , 2022). Entrepreneurial orientation reflects the methods, practices and decision-making styles used by owners or founders to act entrepreneurially (Adam et al , 2022).…”
Section: Introductionmentioning
confidence: 99%